VHF SSB Receiver with Low Consumption - Matoušek, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This work is focused on proposal of SSB receiver operating at 30 MHz. The design was primarily focused on simplicity and low power consumption. This work was realized for the transmission of audio signals. SSB modulation is far more efficient in terms of the radio spectrum used. First part of this thesis describes a block diagram of a receiver. Next parts are focused on proposal of individual blocks of the receiver, especially its most important parts. Finally, the overall evaluations of the design characteristics of SSB receivers are discussed.
Keywords: SSB; low noise amplifier; automatic gain control; AD607